Abnormal Mechanical Loading Induces Cartilage Degeneration by Accelerating Meniscus Hypertrophy and Mineralization After ACL Injuries In Vivo. (March 2016) - Du, Guoqing; Zhan, Hongsheng; Ding, Daofang; Wang, Shaowei; Wei, Xiaochun; Wei, Fangyuan; Zhang, Jianzhong; Bilgen, Bahar; Reginato, Anthony M.; Fleming, Braden C.; Deng, Jin; Wei, Lei
Background: Although patients with an anterior cruciate ligament (ACL) injury have a high risk of developing posttraumatic osteoarthritis (PTOA), the role of meniscus hypertrophy and mineralization in PTOA after an ACL injury remains unknown. Purpose/Hypothesis: The purpose of this study was to determine if menisci respond to abnormal loading and if an ACL injury results in meniscus hypertrophy and calcification. The hypotheses were that (1) abnormal mechanical loading after an ACL injury induces meniscus hypertrophy and mineralization, which correlates to articular cartilage damage in vivo, and (2) abnormal mechanical loading on bovine meniscus explants induces the overexpression of hypertrophic and mineralization markers in vitro. Study Design: Controlled laboratory study. Methods: In vivo guinea pig study (hypothesis 1): Three-month-old male Hartley guinea pigs (n = 9) underwent ACL transection (ACLT) on the right knee; the left knee served as the control. Calcification in the menisci was evaluated by calcein labeling 1 and 5 days before knee harvesting at 5.5 months. Cartilage and meniscus damage and mineralization were quantified by the Osteoarthritis Research Society International score and meniscus grade, respectively. Indian hedgehog (Ihh), matrix metalloproteinase–13 (MMP-13), collagen type X (Col X), progressive ankylosis homolog (ANKH), ectonucleotide pyrophosphatase/phosphodiesterase–1 (ENPP1), alkaline phosphatase (ALP), inorganic pyrophosphate (PPi), and inorganic phosphate (Pi) concentrations were evaluated by immunohistochemistry and enzyme-linked immunosorbent assay. In vitro bovine meniscus explant study (hypothesis 2): Bovine meniscus explants were subjected to 25% strain at 0.3 Hz for 1, 2, and 3 hours. Cell viability was determined using live/dead staining. The levels of mRNA expression and protein levels were measured using real-time quantitative reverse transcription polymerase chain reaction and Western blot after 24, 48, and 72 hours in culture. The conditioned medium was collected for sulfated glycosaminoglycan (GAG) release and Pi/PPi assay. Results: In vivo guinea pig study: Meniscus size and area as well as intensity of meniscus calcification were significantly increased in the ACLT group compared with the control group. Both calcified area and intensity were correlated with cartilage damage in the ACLT group (meniscus calcified area: r = 0.925, P < .0001; meniscus calcified intensity: r = 0.944, P < .0001). Ihh, MMP-13, Col X, ANKH, ENPP1, and ALP expression were increased in the ACLT group compared with the control group. The Pi level and Pi/PPi ratio increased by 63% and 42%, respectively, in the ACLT group compared with the control group. In vitro bovine meniscus explant study: Cell death was found in the superficial zone of the bovine meniscus explants after loading for 3 hours. The mRNA expression and protein levels of MMP-13, ANKH, ENPP1, and ALP were up-regulated in all 3-hour loaded samples. The Pi/PPi ratio and sulfated GAG content in the culture medium were increased in the 3-hour loaded group. Conclusion: Meniscus hypertrophy and mineralization correlated to cartilage degeneration after ACL injuries. Clinical Relevance: The study data suggest that the suppression of meniscus hypertrophy and calcification may decrease the risk of PTOA after ACL injuries.